Komersialisasi dan Tanggung Jawab Pendidikan: Sekelumit Pembicaraan - wan anwar (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
One of crucial pictures of our education recently is expensive education expense. This happen parallel with pragmatism mental on every side of social life. Commercialization and capitalism often become cause of human values destruction that actually should to be preserved by education. Therefore, we have to do awareness movement to change attitude and action of education’s actor. BHP and BHMN (State’s owner legal institution) status, that giving autonomy to education institution to raise fund from community shouldn’t accentuate commercialization of education at school or campus. Its also prevail on entrepreneurial university that its network source from global market capitalism expansion. School and campus must revitalize its public and humanity responsibility to independent, quality, creative, and responsible human. According to Kuntowijoyo, education task and responsibility is on humanizing human (humanization) effort, liberation, and spiritualizing human (transcendent).